REDUPLIKASI DALAM ACARA CATATAN NAJWA DI STASIUN TELEVISI NARASI TV DAN IMPLIKASI TERHADAP PENDIDIKAN - Rizal Efendi; Misra Nofrita; Asih Ria Ningsih (STKIP ROKANIA, 2020)
This study aims to describe the use of reduplication in the Najwa Notes program on the Narasi TV television station namely (a) the form of reduplication, and (b) the meaning of reduplication. The object of this research is the reduplication contained in the Najwa Notes on Narasi TV. Data obtained using the note note method. The research instrument is a human instrument with video aids because the TV shows are researched. Data were analyzed using descriptive qualitative methods. The results of the study are as follows. First, the reduplication forms found are (a) full reduplication, divided into two basic words, there are 55 data and invented words, there are 10 data (b) partial reduplication, found 11 data (c) affixed reduplication, found 13 data , and (d) reduplication with phoneme changes. 2 data found 2. Second, the meaning of reduplication found is (a) noun, stating the meaning resembles 3 data found, plural states, 51 data found (b) verb, stating that work is found 5 times over and over again , stating the work is carried out continuously is found as many as 3 data, stating various meanings, as much as 3 data, stating mutually, as much as 5 data, stating the meaning of relaxing actions as much as 2 data (c) adjectives, stating very, as much as 8 data, stating until, as much as 4 data, states at most, as much as 1 data (d) number words, states for the sake of, as much as 1 data, states specificity, as much as 2 data, states collectively, as much as 1 data. The conclusion of this research is that in the Najwa Notes program on TV Narrative TV station there are forms and meanings of reduplication namely full reduplication of both basic and invented words, partial reduplication, reduplication of affixes, reduplication with phoneme changes and there are also meanings according to the basic words namely nouns, verbs, adjectives, and number words.